(untitled) (Jurnal Teknologi (Sciences & Engineering), 2015)
The usage of recycled rubber in tire production is not common. This paper mainly focuses on feasibility of recycled tire to be used in production, particularly on thermal and rheological behavior of the blended recycled rubber and natural rubber.Â The investigation has been conducted on the blend of recycled rubber (RR) and natural rubber to determine the suitable composition of RR and SMR (Standard Malaysian Rubber) for the manufacturing of tire thread. RR which was taken from the thread of lorry tires was blended with two natural rubber types; SMR-L and SMR-10 at different mass ratio. The thermal characteristic was studied using Differential Scanning Calorimetry (DSC) while Capillary rheometer and Mooney viscometer was used to study the rheology behavior of the blends. It was found that SMR-10 has increased the thermal stability of the blend as opposed to SMR-L. Both natural rubber blends show Â similar relationship between shear viscosity and shear rates but SMR-10/RR blends exhibit higher viscosity than SMR-L/RR blends based on Mooney viscosity analysis.